2020
DOI: 10.1021/acs.jmedchem.9b01813
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the Impact of Lipophilicity on Potency and Pharmacokinetic Parameters Enables the Use of Diverse Chemical Space during Small Molecule Drug Optimization

Abstract: Lipophilicity has a dominant effect on many parameters that determine unbound drug exposure as well as drug potency. Despite this, analysis of a large body of drug data indicates lipophilicity has no consistent directional impact on dose. This can be rationalized based on the interplay of the effects of lipophilicity on individual parameter values in pharmacokinetic equations. We believe this undermines the effectiveness of strategies that target specific ranges for drug parameters for which lipophilicity play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 65 publications
1
69
0
Order By: Relevance
“…This method is not without its limitations, since alterations to lipophilicity has a downstream impact on the PK properties of a molecule. [125,126] Therefore, increasing hydrophilicity might not always be a suitable method if improving solubility. In these instances, an alternative strategy involves reducing molecular planarity and symmetry, thus disrupting crystal packing, and reducing the energy barrier to dissolution.…”
Section: Hydrophilicity Hydrophobicity and Solubilitymentioning
confidence: 99%
“…This method is not without its limitations, since alterations to lipophilicity has a downstream impact on the PK properties of a molecule. [125,126] Therefore, increasing hydrophilicity might not always be a suitable method if improving solubility. In these instances, an alternative strategy involves reducing molecular planarity and symmetry, thus disrupting crystal packing, and reducing the energy barrier to dissolution.…”
Section: Hydrophilicity Hydrophobicity and Solubilitymentioning
confidence: 99%
“…Thus, log P N has been used for predicting the ability of bioorganic compounds to cross cell membranes [ 3 ]. Nowadays, it is still being used for assessing the impact on pharmacokinetic parameters and potency [ 4 ], metabolism and excretion[ 5 , 6 ], and toxicity [ 7 ] of research compounds.…”
Section: Introductionmentioning
confidence: 99%
“…14 We hypothesize that the cellular assay does not accurately reflect the complex tissue environment where TRPA1 channels reside in vivo and that lower lipophilicity compounds may possess a decreased ability to access the membrane-bound TRPA1 channel within the target tissues. 21 In support of this hypothesis, we noticed that larger in vivo potency shifts correlated with lower measured log D 7.4 . While log D 7.4 is a common measure of bulk hydrophobicity, it does not accurately model interactions with zwitterionic phospholipids (i.e., phospholipophilicity) which may impact target access for TRPA1 antagonists bound at the membrane.…”
mentioning
confidence: 99%
“…22 We thought that unbound volume of distribution (V ss,u = V ss /f u ), an in vivo measure of drug distribution in the body, might be a better reflection of the overall tissue (i.e., membrane) binding. 21,23,24 Using rat PK data, we found that molecules with a higher V ss,u possess a reduced potency shift in vivo (see data Table 1). While both log D 7.4 and V ss,u show similar trends, we found V ss,u to be a useful measure of in vivo lipophilicity that helped reconcile PKPD disconnects observed in the program.…”
mentioning
confidence: 99%